Non-coding RNAs from seminal plasma extracellular vesicles and success of live birth among couples undergoing fertility treatment - Oluwayiose, Oladele A.; Houle, Emily; Whitcomb, Brian W.; Suvorov, Alexander; Rahil, Tayyab; Sites, Cynthia K.; Krawetz, Stephen A.; Visconti, Pablo E.; Pilsner, J. Richard (Frontiers in Cell and Developmental Biology, 2023)
Background: Infertility remains a global health problem with male-factor infertility accounting for around 50% of cases. Understanding the molecular markers for the male contribution of live birth success has been limited. Here, we evaluated the expression levels of seminal plasma extracellular vesicle (spEV) non-coding RNAs (ncRNAs) in men of couples in relation with those with and without a successful live birth after infertility treatment. Method: Sperm-free spEV small RNA profiles were generated from 91 semen samples collected from male participants of couples undergoing assisted reproductive technology (ART) treatment. Couples were classified into two groups based on successful live birth (yes, n = 28) and (no, n = 63). Mapping of reads to human transcriptomes followed the order: miRNA > tRNA > piRNA > rRNA> “other” RNA > circRNA > lncRNA. Differential expression analysis of biotype-specific normalized read counts between groups were assessed using EdgeR (FDR<0.05). Result: We found a total of 12 differentially expressed spEV ncRNAs which included 10 circRNAs and two piRNAs between the live birth groups. Most (n = 8) of the identified circRNAs were downregulated in the no live birth group and targeted genes related to ontology terms such as negative reproductive system and head development, tissue morphogenesis, embryo development ending in birth or egg hatching, and vesicle-mediated transport. The differentially upregulated piRNAs overlapped with genomic regions including coding PID1 genes previously known to play a role in mitochondrion morphogenesis, signal transduction and cellular proliferation. Conclusion: This study identified novel ncRNAs profiles of spEVs differentiating men of couples with and without live birth and emphasizes the role of the male partner for ART success.